(untitled) (Journal of Hama University, 2025)
The Aim: The current study aimed to compare the rate of speed movement of upper molar Distalization and total treatment time between a group of Coil Spring Anchored by Mini Implants , a Carrier appliance group, and a Distal Jet appliance group in Class II malocclusion patients. Materials and Methods: 51 patients aged 12-14 with Class II malocclusion were selected for the current study. They were randomly divided into three groups of 17 patients each. The first group received Forsus springs anchored by mini implants, the second group received Carrier appliances from the upper canine to the first upper molar on both sides, and the third group received Distal jet appliances. The transverse movement speed of the upper first molars and the total time for correction were evaluated in all three groups from the start of orthodontic treatment until completion of correction and achieving a Class I relationship. Results: The mean value of the velocity of distalization movement speed in Group 2 (Carrier) (1.18 and 0.84) was higher compared to Group 1 (Springs) and Group 3 (Distal jet) by a significant difference of 0.001, respectively. Additionally, the mean total retention time in Group 2 (5.48) was for Group 1 and (4.91) for Group 3, with an average velocity of movement around 1.5 in Group 2, while the average total retention time was about 3 months in Group 2, 7 months in Group 3, and 9 months in Group 1. Conclusions: Processing with the Carrier appliance resulted in faster initial upper molar distalization movement speed and overall distalization time compared to the spring anchored by mini implants group and Distal jet group.